1986
DOI: 10.1111/j.1600-0536.1986.tb01194.x
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of contact sensitizers in resins and products based on phenol‐formaldehyde

Abstract: 12 phenol-formaldehyde resins were investigated with regard to the presence of 14 contact sensitizers by using high-pressure liquid chromatography. The allergens consisted of simple methylol phenols, dihydroxydiphenyl methanes, 4,4(1)-dihydroxy-(hydroxymethyl)-diphenyl methanes and 2,4(1)-dihydroxy-(hydroxymethyl)-diphenyl methanes. Four substances, 2,4-dimethylol phenol, 2,6-dimethylol phenol, 4,4(1)-dihydroxydiphenyl methane and 2,4(1)-dihydroxydiphenyl methane, were isolated from a resol resin and identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
70
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(74 citation statements)
references
References 7 publications
0
70
0
Order By: Relevance
“…Identifying the clinical relevance of any sensitizer is not standardized, and it would be necessary to have the capacity to analyse chemically the presence of the 14 separate individual sensitizers identified in PFR‐2, a task that very few centres in the world could perform. PFRs are known to be both irritants and potent sensitizers, and contain methylol‐substituted monomers and dimers, which are the major sensitizers (1, 7). As stated earlier, the common PTBP‐FR does not detect contact allergy to PFRs based on phenol and formaldehyde, and patients allergic to this latter resin will be missed if PFR‐2 is not tested.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Identifying the clinical relevance of any sensitizer is not standardized, and it would be necessary to have the capacity to analyse chemically the presence of the 14 separate individual sensitizers identified in PFR‐2, a task that very few centres in the world could perform. PFRs are known to be both irritants and potent sensitizers, and contain methylol‐substituted monomers and dimers, which are the major sensitizers (1, 7). As stated earlier, the common PTBP‐FR does not detect contact allergy to PFRs based on phenol and formaldehyde, and patients allergic to this latter resin will be missed if PFR‐2 is not tested.…”
Section: Discussionmentioning
confidence: 95%
“…A p ‐tertiary‐butylphenol‐formaldehyde resin (PTBP‐FR) has been included in most baseline patch test series for decades, but this resin does not detect contact allergy to phenol‐formaldehyde resins (PFRs) based on phenol and formaldehyde (1–4). Even though there are various resins based on phenol and formaldehyde, PFR‐2 (mixture of monomers and dimers from a resol resin based on phenol and formaldehyde) seems to be a good marker for contact allergy to such resins (1, 3, 5). In the past, it was shown that not only did patch testing with PFR‐2 detect patients allergic to the specific resol resin, but simultaneous allergic reactions were also seen to fragrance mix I (FM I), colophonium, and Myroxylon pereirae (6).…”
mentioning
confidence: 99%
“…5 out of a total of 20 machine operators were referred to our department and were patch tested with our standard series and isocyanates series. The standard series used at our department at the time comprised the European standard series excluding clioquinol, N‐isopropyl‐N‐phenyl‐4‐phenylenediamine, lanolin alcohol and supplemented with diazolidinyl urea, imidazolidinyl urea, thimerosal, methyldibromo glutaronitrile, phenoxyethanol, Euxyl K400, iodopropynyl butylcarbamate, DMDM hydantoin, gold sodium thiosulfate (1), palladium chloride, a resol resin based on phenol and formaldehyde (2), ethylenediamine dihydrochloride, lichen acid mix, tixocortol pivalate, hydrocortisone‐17‐butyrate, frullanolide, fusidic acid, caine mix II, tosylamide formaldehyde resin, a textile colour mix, Amerchol L‐101 and an epoxy resin based on diglycidyl ether of bisphenol F. The isocyanates series used comprised the isocyanate series from Chemotechnique Diagnostics, Malmö, Sweden, supplemented with dicyclohexylmethane‐4,4′‐diisocyanate (Aldrich Chemical Company Inc, Milwaukee, USA), synonymous with hydrogenated MDI (HMDI) and its corresponding amine, dicyclohexylmethane‐4,4′‐diamine (Fluka Chemie GmbH, Buchs, Switzerland), synonymous with hydrogenated 4,4′‐diaminodiphenylmethane (HMDA). The first 3 patients referred to us were also patch tested with the polyurethane lacquer used at the plant.…”
Section: Methodsmentioning
confidence: 99%
“…The described circumstances imply that the inclusion of any formaldehyde releaser in the baseline series should be based on the results of parallel routine testing with formaldehyde and the formaldehyde relcaser in question with optimized patch-test doses obtained with standardized patch-test techniques. There was no association between patients reacting to formaldehyde and the resins or plastics in which formaldehyde is used as a raw material, a phenomenon commented on in an earlier study (6).…”
Section: Discussionmentioning
confidence: 86%
“…At our department patch-testing with formaldehyde 2.0% has been used in patients with doubtful reactions to formaldehyde 1.0% and when there has been a strong suspicion of contact allergy to formaldehyde. For more than 25 years, defined micro-pipetted volumes have been used routinely at our department for patch-testing liquid solutions (6). According to our findings, 15 ^1 is optimal for the Finn Chamber technique (7).…”
mentioning
confidence: 95%